Ghazwul Fikri Sebagai Pelemah Keyakinan Umat Islam Generasi Milenial di Era Digital - Risa Nur Laila; Maghfira Adha Nurunnisa; Kameela Munayya Tasneem; Usup Romli (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2022)
The development of technology and the dissemination of information in the digital era has made ghazwul fikri carried out by the West as a form of revenge on Muslims due to the defeat during the Crusade. In this regard, this study aims to understand the form of ghazwul fikri, the dangers of ghazwul fikri as a weakening of Muslim beliefs and how to protect oneself from ghazwul fikri. The literature study method was used in this research. Based on the results of the study, ghazwul fikri, or war of thought is an attempt to attack Muslims from the aspect of idealism, mindset, and image of Muslims. So to protect ourselves from this, as Muslims, we must continue to study Islamic history, examine the truth of Islamic teachings, do good deeds, form a strong personality and character of faith, increase brotherhood, unity, and unity of the people and convey Islamic teachings to the fullest to the successors of civilization. Islam in various occasions and places.